Influence of intra-event-based flood regime on sediment flow behavior from a typical agro-catchment of the Chinese Loess Plateau - Zhang, Le-Tao; Li, Zhan-Bin; Wang, He; Xiao, Jun-Bo (Journal of hydrology (Amsterdam), 2016)
[Display omitted] •Intra event-based flood regimes were analyzed at catchment scale.•Sediment flow behavior under different flood regimes was discussed.•Sediment reduction caused by runoff self-regulation should not be neglected. The pluvial erosion process is significantly affected by tempo-spatial patterns of flood flows. However, despite their importance, only a few studies have investigated the sediment flow behavior that is driven by different flood regimes. The study aims to investigate the effect of intra-event-based flood regimes on the dynamics of sediment exports at Tuanshangou catchment, a typical agricultural catchment (unmanaged) in the hilly loess region on the Chinese Loess Plateau. Measurements of 193 flood events and 158 sediment-producing events were collected from Tuanshangou station between 1961 and 1969. The combined methods of hierarchical clustering approach, discriminant analysis and One-Way ANOVA were used to classify the flood events in terms of their event-based flood characteristics, including flood duration, peak discharge, and event flood runoff depth. The 193 flood events were classified into five regimes, and the mean statistical features of each regime significantly differed. Regime A includes flood events with the shortest duration (76min), minimum flood crest (0.045ms−1), least runoff depth (0.2mm), and highest frequency. Regime B includes flood events with a medium duration (274min), medium flood crest (0.206ms−1), and minor runoff depth (0.7mm). Regime C includes flood events with the longest duration (822min), medium flood crest (0.236ms−1), and medium runoff depth (1.7mm). Regime D includes flood events with a medium duration (239min), large flood crest (4.21ms−1), and large runoff depth (10mm). Regime E includes flood events with a medium duration (304min), maximum flood crest (8.62ms−1), and largest runoff depth (25.9mm). The sediment yield by different flood regimes is ranked as follows: Regime E>Regime D>Regime B>Regime C>Regime A. In terms of event-based average and maximum suspended sediment concentration, these regimes are ordered as follows: Regime E>Regime D>Regime C>Regime B>Regime A. Regimes D and E produce the most runoff volume and the largest amount of sediments, which indicates that these regimes must be at the focus of runoff regulation to control the sediments. Given that the event flood runoff depth remains constant, the sediment yield by different flood regimes is regulated to varying degrees by altering the event-based runoff–sediment relationship. Compared with Regime A, the average decrease rates in the area-specific sediment yield for Regimes B, C, and D are 33%, 78%, and 62%, respectively. The regulative effect of the flood regime conversion on sediment export can be described with several variables that indicate the depth-specific characteristics of individual flood events. Flood regimes indicate the runoff erosivity dynamics and the runoff energy dissipation rates in eroding soil and delivering sediments. Therefore, the flood-regime-dependent sediment flow behavior differs across all regimes. Overall, the predominated controlling factors that influence the final sediment export are regime based. Empirical regime-based runoff–sediment relationships were established via multiple stepwise regressions. The suspended sediment concentration that is driven by different flood regimes can be described by the power function or logarithmic–linear function of runoff-related variables, including instantaneous discharge, runoff erosive power, and event-based flow variability. The regressive equations can explain the major driving forces behind the suspended sediment concentration dynamics. This study highlights the potentials of runoff self-regulation in controlling soil erosion and sediment delivery. The results may provide some evidence for flood regime classification, improve the overall evaluation of the sediment reduction benefits of the runoff regulation system, enrich runoff regulation theory, and improve the runoff control at the catchment scale.